Laparoscopic findings of subfertile female patients in a tertiary hospital. - Anwary, SA; Alfazzaman, M; Nasreen, ZA (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Jul;20(3):391-396 The abstract of this article is available on the PubMed website